Effect of air voids on pavement thermal properties - Hassn, Abdushafi Alhashmi (2017)
Harvesting Energy stands as one of the most promising techniques for approaching the global energy problem without depleting natural resources. Pavement solar energy harvesting (PSEH) technology is one of these techniques and it is considered as a new research area and currently under development which aims to enhance pavements for capture, and storage of thermal energy.